Thirteenth and Fourteenth Century European-Mongol Relations - Ho, Colleen (History compass, 2012)
Growing recent interest in the Mongol Empire and its Eurasian conquests has led to an increase in scholarship on the Mongols. After the Mongol attacks on Eastern Europe - specifically Russia, Poland, Hungary, and the Balkans - in the 1230s-1240s, Europeans were petrified of the terrifying and unfamiliar invaders. However, at times this initial anxiety waned and even turned to hope for a European alliance with the Mongols against Muslim powers like the Mamlūks of Egypt. This essay briefly summarizes recent major works on medieval European and Mongol relations in the areas of diplomacy, mission, art, and material culture. The author encourages scholars on the Mongol Empire to collaborate across disciplines in an attempt to counteract the difficult multilingual nature of sources on the Mongol Empire. Finally, the essay will show how medieval Eurasian and Mongol studies exemplify topics in history like transnationalism, cross-cultural exchanges, and intercontinental trade, which are more relevant today in our globalized world than ever.